Penerapan Penggunaan Aplikasi Multiplatform Dalam Pengajaran Bahasa Inggris Di MTS Nurul Falah Areman Depok - Hanna Sundari; Rina Husnaini Febriyanti (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Abstract-This community service activity was held in MTs Nurul Falah Areman Depok that the purposes were to share knowledge and information about how to use Multiplatform Application for teaching English in junior high school level. This activity was not only to give explanation in theoretically but also practically about using Multiplatform Application involved detailed within applying it to method and technique during in teaching and learning process. The community service activity was a training to the teachers who teach in MTs Nurul Falah Areman. In that training was applied the simulation and practiced directly towards the teachers how to use Multiplatform Application for teaching. The method used during community service was Community Language Learning where the activity filled with sharing and discussing among participants such as consultant and client. The result was by the community service activity that the partner felt interesting and glad towards to its. Keywords: Multiplatform Application, Teaching English, English Teachers